Lifter assignment problem for inter-line transfers in semiconductor manufacturing facilities. Issue 5 (September 2016) - Na, Byungsoo; Woo, Jung-Eun; Lee, Junho
Abstract As more advanced and diverse semiconductor products are demanded, each product requires more processing steps, and the product mix changes frequently. The production volume may exceed the capacity of one line at a semiconductor fabrication plant, and the equipment utilization becomes unbalanced. This situation leads to a combination of multiple lines, which requires the transfer of wafer lots from one line to another. Lifters are machines for inter-line transfers, and they can quickly become a critical bottleneck of semiconductor manufacturing. We introduce an online assignment problem between lifters and inter-line transfers, which is motivated in unified automated material handling systems. We propose several solution methods to improve assignment efficiency and resolve inter-line transfer delays in material handling systems. When compared to the round robin method used currently, the shortest expected arrival time (SEAT) rule decreases delivery time by 8.9 %.